Biochemical Composition and Bioactive Properties of Chlorella minutissima (Chm1) as a Potential Source of Chemical Compounds for Nutritional Feed Supplement and Disease Control in Aquaculture - Arguelles*, Eldrin DLR. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2020)
Microalgae contain high levels of proteins, lipids, carbohydrates and other bioactive metabolites with direct relevance to aquaculture. This investigation was done to assess the bioactive properties and describe the neutraceutical and pharmacological benefits of a green microalga, Chlorella minutissima (Chm1). The alga has a total phenolic content of 30.94±0.06 mg GAE g-1. Relative antioxidant efficiency showed that C. minutissima exerted potent ABTS scavenging activity and high ability of reducing copper ions in a concentration-dependent manner with IC50 values of 48.13 μg GAE ml-1 and 13.90 μg GAE ml-1, respectively. Evaluation of antibacterial activities using microtiter plate dilution assay revealed that C. minutissima showed strong activity against Aeromonas hydrophila with a minimum inhibitory concentration (MIC) of 125 μg ml-1. The algal extract is also effective against Vibrio cholerae, Vibrio parahaemolyticus and Staphylococcus aureus in each case with MIC value of 250 μg ml-1. Also, C. minutissima extract was able to inhibit the growth of Pseudomonas fluorescens with MIC value of 500 μg ml-1. Proximate composition of the dried microalga showed that C. minutissima consists of high protein, ash and crude fat content with values of 42.61±0.11%, 17.79 ± 0.04% and 11.70 ± 0.01%, respectively. The results show that C. minutissima is an excellent candidate organism as a potential source of chemical compounds important for feed formulation and disease control in aquaculture. Keywords: Antibacterial activity; antioxidant activity; bioactive compounds; bacterial fish pathogen; Chlorella; microalgae; proximate analysis *Corresponding author: Tel.: +6349-536-2884 Fax: +6349-536-2721 E-mail: edarguelles@up.edu.ph